When is the gift given? Organ donation, social representations, and an opportunity to register. (3rd February 2019) - Moloney, Gail; Sutherland, Michael; Norton, Maddison; Walker, Iain
Abstract: The gift of life doctrine underpins Australia's approach to organ donation: in legislation, clinical practice, community awareness campaigns, and educational activities. In this paper, we present an approach that situates an understanding of organ donation within a social representation framework as a system of values, ideas, and practices. In cadaveric donation, the final giving‐of‐the‐gift can never be by the donor, leading us to ask where the potential donor's decision to give the gift really lies. We present research from three studies that explored the relationship between what was socially understood about organ donation and the registration of donation intent. Drawing from three socially and culturally diverse populations, we asked people working in a corporate city institution and those attending two football matches in the outer city area to complete a word‐association task and Likert‐scale belief questions about organ donation—followed by an opportunity to register immediately on the Australian Organ Donor Register. Driven by the interdependent themata of life/death and self/other, the gift of life doctrine is inextricably linked with the loss of life emerging as both positive and negative beliefs allowing their relationship to actual registration behaviour to be observed. Our findings suggest that in many instances, the potential donor's genuine desire to give the gift lies in the tension between positive and negative beliefs, manifesting as a consent registration when the positive beliefs about donation prevail and an immediate opportunity to register is available.